The Effect of Intellectual Capital on Financial Company: Empirical Study from Indonesia - Entis Sutisna; Fahrudin Pasolo; Entar Sutisman; Lina Mariana (PT Mattawang Mediatama Solution, 2023)
This study examines: 1) The Effect of Value-Added Capital Employed (VACA) on Financial Performance. 2) Effect of value-added human capital (VAHU) on financial performance 3) Effect of Structural Capital Value Added (STVA) on Financial Performance. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The number of companies studied was 41. The sampling technique used was purposive. The type of sample is obtained based on predetermined criteria. The data used is quantitative data obtained in the form of numbers that can be calculated by accessing the IDX.co.id site and the official website of each company. The data analysis technique used is multiple regression analysis. The study results show that: 1) Value Added Capital Employed (VACA) positively and significantly affects financial performance. 2) Value-added human capital (VAHU) has a positive and insignificant effect on financial performance. 3) Structural Capital Value Added (STVA) positively and significantly affects financial performance.